Examples & exercises in operations research - Ghosal, A.; Loo, S. G.; Singh, Nau Nihal (London ; New York : Gordon and Breach Science Publishers, 1975)
Techniques are taught through examples and exercises. its principal aim is to satisfy queries of students at a lower level and users of Operations Research who would refer to the book for solution of real-life problems.
Includes bibliographical references and index.
ucj 18/01/2019
Loans
Keywords: Operations research